Policy asymmetries, endogenous market structure with multinational corporations and the pattern of commodity trade - Pertti Haaparanta; Mikko Spolander (Bank of Finland, 1991)
The impact of asymmetries in trade and industrial policies on the market structure and location of firms and on the pattern of commodity trade are examined using a model in which firms have to take the decisions of other firms into account because of imperfect competition. This approach allows us to consider the implications of policy harmonization in contrast to overall liberalization of, for example, trade policies. Among the main results are that policy asymmetries can lead to equilibria where only firms (all active) of unequal size can coexist and where the locational decisions of some firms are aggressive in the sense that the position of other firms is made worse. Policy asymmetries increase competition in the markets. It is also argued that policy asymmetries push trade towards inter-industry trade while with symmetric policies intra-industry trade is observed. The welfare effects of policy harmonization are ambiguous. Inter-industry trade occurs because policy asymmetries tend to concentrate industries in the same place.
URN:NBN:fi:bof-201908081369
Keywords: 330